PERAN EMOSI DALAM MEMEDIASI PERSEPSI KEADILAN TERHADAP KEPUASAN PASCA PEMULIHAN - Ken Sudarti (STIE Pelita Nusantara Semarang, 2013)
A company will not be separated from the failure when the company deliver services. Companies that have high quality standards will not be easy though to avoid failure. This failure will result in dissatisfaction and complaint behavior, so companies have to implement service recovery. Consumers who submit complaints and feel recovery services will assess whether they are being treated fairly or not. Justice can be viewed from three dimensions, namely distributive justice, procedural justice and interactional justice. If consumers are treated fairly, then this will have an effect on positive emotions and post-recovery satisfaction. This customer emotions will affect the post-recovery satisfaction.